The impact of chronic kidney disease: experiences of patients and relatives from the extreme north of Brazil - Maria Virgínia Filgueiras de Assis Mello; Margareth Angelo (Investigación y Educación en Enfermería, 2018)
Objective. To identify the impact of chronic kidney disease on patients and their families.